2017
DOI: 10.1002/mnfr.201600804
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α‐cyclodextrin reduces atherosclerosis and modifies gut flora in apolipoprotein E‐deficient mice

Abstract: Scope α-Cyclodextrin (α-CD), a cyclic polymer of glucose, has been shown to lower plasma cholesterol in animals and humans; however, its effect on atherosclerosis has not been previously described. Methods and Results apoE-knockout mice were fed either low-fat diet (LFD; 5.2% fat, w/w), or Western high fat diet (21.2% fat) containing either no additions (WD), 1.5% α-CD (WDA); 1.5% β-CD (WDB); or 1.5% oligofructose-enriched inulin (WDI). Although plasma lipids were similar after 11 weeks on the WD vs. WDA die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…Thus, the increases of these bacterial species by supplementation of α‐CD in obese mice may be beneficial as an antiobesity treatment. Sakurai et al reported that 1.5% of α‐CD administration decreased the Clostridium proportion in apolipoprotein E‐deficient mice, which is similar to the effect of 5.5% α‐CD on Clostridium spp. in this study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, the increases of these bacterial species by supplementation of α‐CD in obese mice may be beneficial as an antiobesity treatment. Sakurai et al reported that 1.5% of α‐CD administration decreased the Clostridium proportion in apolipoprotein E‐deficient mice, which is similar to the effect of 5.5% α‐CD on Clostridium spp. in this study.…”
Section: Discussionmentioning
confidence: 73%
“…A previous study showed that Bacteroides ovatus decomposes α‐CD by producing cyclodextrinase . Recently, it was reported that addition of α‐CD (1.5% w/w) to a HFD at relatively low doses reduces atherosclerosis in apolipoprotein E‐deficient mice . This effect may be associated with gut microbiota modulation.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, oral administration of ACD has been shown to reduce levels of proatherogenic lipoproteins and improve fatty acid profiles in LDLr-knock out (KO) mice fed a high-fat/high-cholesterolcontaining diet . Furthermore, oral administration of ACD reduced atherosclerotic lesion size, with only minimal change in plasma lipids, but was associated with potential beneficial changes in gut flora in apoE-KO mice 26 . In humans, oral intake of ACD has also been shown to have beneficial effects.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…In these CDs, αCD is widely used as a water-soluble dietary fibre 8 . Addition of 1.5% αCD to mice has been shown to decrease the numbers of caecal bacteria belonging to the genus Clostridium 9 . In contrast, dextran is produced by lactic acid bacteria of the genera Leuconostoc , Streptococcus , Lactococcus , and Lactobacillus 10 .…”
Section: Introductionmentioning
confidence: 99%